Tafsir Ilmi Versus Tafsir Ilmi: Ants in Scientific Interpretation Discourses - Shabriyah, Nabila Shema; Miski, Miski (Ushuluddin, Adab, and Dakwah Faculty of State Islamic University Ponorogo, 2023)
This article is based on the Ayat-Ayat Semes ta dan Nalar Ayat-ayat Semesta written by Agus Purwanto and Tafsir 'Ilmi: Animals in the Perspective of the Qur'an and Science published by Lembaga Pentashih Mushaf al-Qur'an (LPMQ) of the Ministry of Religious Affairs of Indonesia in collaboration with the Indonesian Institute of Sciences with a focus on the interpretation of the word